Myb via TGFβ is required for collagen type 1 production and skin integrity - Sampurno, S.; Cross, R.; Pearson, H.; Kaur, Pritinder; Malaterre, J.; Ramsay, R. (JAI Press, 2015)
Skin integrity requires an ongoing replacement and repair orchestrated by several cell types. We previously investigated the architecture of the skin of avian myeloblastosis viral oncogene homolog (Myb) knock-out (KO) embryos and wound repair in Myb+/− mice revealing a need for Myb in the skin, attributed to fibroblast-dependent production of collagen type 1. Here, using targeted Myb deletion in keratin-14 (K14) positive cells we reveal further Myb-specific defects in epidermal cell proliferation, thickness and ultrastructural morphology. This was associated with a severe deficit in collagen type 1 production, reminiscent of that observed in patients with ichthyosis vulgaris and Ehlers–Danlos syndrome. Since collagen type 1 is a product of fibroblasts, the collagen defect observed was unexpected and appears to be directed by the loss of Myb with significantly reduced tumor growth factor beta 1 (Tgfβ−1) expression by primary keratinocytes. Our findings support a specific role for Myb in K14+ epithelial cells in the preservation of adult skin integrity and function.